High density lipoprotein proteome is associated with cardiovascular risk factors and atherosclerosis burden as evaluated by coronary CT angiography. (November 2018) - Gordon, Scott M.; Chung, Jonathan H.; Playford, Martin P.; Dey, Amit K.; Sviridov, Denis; Seifuddin, Fayaz; Chen, Yun-Ching; Pirooznia, Mehdi; Chen, Marcus Y.; Mehta, Nehal N.; Remaley, Alan T.
Abstract: Background and aims: High density lipoprotein cholesterol (HDL-C) is associated with risk of cardiovascular disease (CVD); however, therapeutic manipulations of HDL-C have failed to reduce CVD events. This suggests that HDL-C and the atheroprotective capacity of HDL are not directly linked. The goal of this study was to evaluate the relationships between HDL-bound proteins and measures of atherosclerosis burden and HDL function. Methods: The HDL proteome was analyzed using mass spectrometry in 126 human subjects, who had undergone coronary computed tomography angiography (CCTA) to quantify calcified (CB) and non-calcified (NCB) atherosclerosis burden. Partial least squares regression analysis was used to evaluate associations between HDL-bound proteins and CB, NCB, or cholesterol efflux capacity (CEC). Results: Significant overlap was found among proteins associated with NCB and CEC. Proteins that were associated with NCB displayed an inverse relationship with CEC, supporting a link between this protective function of HDL and clinical plaque burden. CB was associated with a set of proteins mostly distinct from NCB and CEC. When CVD risk factors were evaluated, BMI had a stronger influence on important HDL proteins than gender, age, or HDL-C. Most HDL proteins associated with function or atherosclerosis burden were not significantly correlated with HDL-C. Conclusions: These findings indicate that the HDL proteome contains information not captured by HDL- C and, therefore, has potential for future development as a biomarker for CVD risk. Additionally, the proteome effects detected in this study may provide HDL compositional goals for evaluating new and existing HDL-modification therapies. Graphical abstract: Highlights: The human HDL proteome is associated with HDL function and atherosclerosis burden. Traditional CVD risk factors influence the HDL proteome, especially BMI. HDL proteins that influence cholesterol efflux also associate with soft plaque. Calcified plaque is associated with a unique HDL proteome signature.